2017
DOI: 10.1002/joc.5098
|View full text |Cite
|
Sign up to set email alerts
|

Further inquiry into characteristics of MJO in boreal winter

Abstract: The characteristics of Madden–Julian Oscillation (MJO), especially over the equatorial western Pacific, during the boreal winter (November to March) have got a further investigation based on the reanalysis data. The MJO activity prevails over the equatorial Indian Ocean and western Pacific and its main active centres are in the Southern Hemisphere. The MJO also has the highest percentage in the atmospheric variability and strong interannual variability here. The MJO over the equatorial western Pacific shows a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…For example, Slingo et al (1999) showed an increasing trend of interannual MJO activity since 1958, by analyzing the variances of bandpass (20-100 days) filtered u200 and u850 averaged between 10°S and 10°N. Chen et al (2017) also defined an MJO intensity index in a similar way (amplitude of u850 averaged over 10°S-10°N, 120-160°E) in his study of interannual and interdecadal MJO variability during 1861-2010. Another method reflecting MJO activity is to compute the two leading PCs of MJO circulation responses, such as u200, u850, velocity potential, stream function or combinations of them (Slingo et al 1999;Jones and Carvalho 2006;Ventrice et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Slingo et al (1999) showed an increasing trend of interannual MJO activity since 1958, by analyzing the variances of bandpass (20-100 days) filtered u200 and u850 averaged between 10°S and 10°N. Chen et al (2017) also defined an MJO intensity index in a similar way (amplitude of u850 averaged over 10°S-10°N, 120-160°E) in his study of interannual and interdecadal MJO variability during 1861-2010. Another method reflecting MJO activity is to compute the two leading PCs of MJO circulation responses, such as u200, u850, velocity potential, stream function or combinations of them (Slingo et al 1999;Jones and Carvalho 2006;Ventrice et al 2013).…”
Section: Introductionmentioning
confidence: 99%